PERLINDUNGAN HUKUM TERHADAP PT PEGADAIAN ATAS BARANG JAMINAN HASIL TINDAK PIDANA PENCURIAN (STUDI PUTUSAN NOMOR 150/PID.B/2023/PN.KTG.) - Sitorus, Steven; Prasetyo, Boedi (Universitas Muhammadiyah Ponorogo, 2024)
This research examines the legal protection for PT Pegadaian on pawn collateral that is proven to be the result of a criminal offense, such as in the case of Kotamobagu District Court Decision Number 150/Pid.B/2023/PN.Ktg. The purpose of this study is to examine the availability of legal protection. to PT Pegadaian and the legal actions that may be done in the event that problematic material is encountered. This study employs a normative legal approach that draws on statutes and case law and adopts the theory of preventive and repressive legal protection. The results show that although PT Pegadaian has applied the precautionary principle following the Standard Operating Procedure (SOP), there is still a risk of receiving collateral from criminal acts that can cause material and immaterial losses. Therefore, a clearer legal protection mechanism is needed to maintain trust in the relationship between debtors and creditors and ensure legal certainty in business activities.